Midlife mortality in White non-Hispanic male veterans enrolled in Department of Veterans Affairs primary care, 2003–2014. Issue 1 (January 2020) - Liu, Chuan-Fen; Hebert, Paul; Wong, Edwin S.; Nelson, Karin; Maynard, Charles
Abstract: Background: After years of decline in mortality rates in the United States, there have been increases in mortality rates in White non-Hispanic Americans ages 45–54, due to increases in deaths from suicide, poisoning, and alcoholic liver disease. Objectives: To determine whether White non-Hispanic middle age male Veterans enrolled in Department of Veterans Affairs (VA) primary care had increased mortality, as found in the general population. Research design: Repeated cross-sectional analysis over 12 years to describe trends in death rates for men across 3 race/ethnicity groups (White non-Hispanic, Black non-Hispanic, Hispanic) and 2 age groups (45–54, 55–64) for the Veteran and general US male populations. Subjects: 60 million patient-years for Veterans enrolled in VA primary care from 2003 to 2014 and 1.8 million who died during the study period. Measures: All-cause and cause specific death rates for alcoholic liver disease, poisoning, and suicide. Results: For White non-Hispanic male Veterans ages 55–64, the increase in all-cause mortality from 2003 to 2014 (+309 deaths/100, 000) was accompanied by significant changes in deaths due to poisoning (+30/100, 000), alcoholic liver disease (+23/100, 000), and suicide (+17/100, 000). For US men ages 55–64, all-cause mortality decreased slightly from 2003-2014 (-22 deaths/100, 000). However, there were increases in death rates due to poisoning (+17/100, 000), alcoholic liver disease (+14/100, 000) and suicide (+11/100, 000). Conclusions: These disturbing findings for White non-Hispanic Veteran men ages 55–64 suggest the critical importance of suicide prevention programs as well as the importance of high quality integrated health care for both Veteran and non-Veteran men. Abstract : Epidemiology; Health sciences; Internal medicine; Clinical research; Social sciences; Sociology; Veterans; Cause of death; Mortality trends